Computation of Benzenoid Planar Octahedron Networks by Using Topological Indices. (20th April 2023) - Ali, Didar Abdulkhaleq; Ali, Haidar; Ain, Qurat Ul; Kirmani, Syed Ajaz K.; Ali, Parvez; Sesay, Mohamed
Abstract : Chemical descriptors are numeric numbers that contain a basic chemical structure and describe the structure of a graph. A graph's topological indices are linked to its chemical characteristics. Biological activity of chemical compounds can be predicted using topological indices. Numerous chemical indices have been developed in theoretical chemistry, including the Zagreb index, the Randić index, the Wiener index, and many others. In this paper, we compute the exact results for the Randić, Zagreb, Harmonic, augmented Zagreb, atom-bond connectivity, and geometric-arithmetic indices for the Benzenoid networks theoretically.